0231 Daily relationships between sleep and stress during the COVID-19 pandemic: Roles of perseverative cognition and physical activity. (25th May 2022) - Baron, Kelly; Shoaf, Kimberley; Nicholls, Connor; Tobin, Selene; Halliday, Tanya; Prather, Aric; Qeadan, Fares
Abstract: Introduction: The onset of the COVID-19 pandemic disrupted and changed sleep as well as elevated stress levels worldwide. Previous research has demonstrated a bidirectional relationship between stress and sleep, in that stress contributes to poorer sleep and poor sleep leads to higher stress. It is hypothesized that perseverative cognition (i.e., worry, racing thoughts) is a key cognitive mechanism in this relationship. The goal of our study was to examine the relationships between stress and sleep during a major global stressor, testing key cognitive and behavioral factors that may influence this relationship. Methods: Adults aged 18 and above were recruited to complete a text-message survey twice per day for 3 weeks over a 4-month period. Sleep duration and efficiency during the previous night and evening/overnight perseverative cognition was measured in the morning survey, daily stress levels were measured in the evening survey. Physical activity was measured by the International Physical Activity Questionnaire (IPAQ). Results were analyzed using mixed effects models controlling for age, gender and race/ethnicity. Results: Participants included 191 adults (91 F, mean age= 43, SD= 16 years). Results demonstrate that stress ratings were associated with higher sleep duration (p= 0.04) but perseverative cognition was associated with lower sleep duration and efficiency (p values <0.001). Participants who were more physically active had higher sleep duration (p=0.02) and efficiency (p< 0.001). Sleep did not predict next-day stress. Conclusion: Results demonstrate that perseverative cognition is a key factor in the daily relationships between stress during the day and sleep at night. Higher physical activity was related to better sleep. These results indicate that interventions to reduce perseverative cognition may improve sleep during times of stress, including reducing the sleep-disrupting effects of the COVID-19 pandemic. Support (If Any): University of Utah i3 COVID-19 pilot grant, UL1TR002538